2015
DOI: 10.1073/pnas.1516779112
|View full text |Cite
|
Sign up to set email alerts
|

Topological analyses in APP/PS1 mice reveal that astrocytes do not migrate to amyloid-β plaques

Abstract: Although the clustering of GFAP immunopositive astrocytes around amyloid-β plaques in Alzheimer's disease has led to the widespread assumption that plaques attract astrocytes, recent studies suggest that astrocytes stay put in injury. Here we reexamine astrocyte migration to plaques, using quantitative spatial analysis and computer modeling to investigate the topology of astrocytes in 3D images obtained by two-photon microscopy of living APP/PS1 mice and WT littermates. In WT mice, cortical astrocyte topology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
3
26
2
Order By: Relevance
“…The reduction in global versus the increase in clustered GFAP coverage is in line with a previous study where general astroglial cytoskeletal atrophy was observed, while GFAP+ astrocytes surrounding Aβ plaques were hypertrophic in the HPC of 18-month-old 3xTG AD mice [77]. Given that astrocytes do not migrate to amyloid plaques [78], current data suggests that astrocytes near plaques are induced to upregulate GFAP expression, while astrocytes in the rest of the HPC downregulate GFAP. As many extracellular factors, e.g., inflammatory factors, can affect transcription and translation of GFAP [79,80], microenvironmental changes induced by plaque accumulation may lead to local dynamic alterations in GFAP expression.…”
Section: Modulation Of Astrocytes By Aβ Overexpression In Hpc and Ecsupporting
confidence: 91%
“…The reduction in global versus the increase in clustered GFAP coverage is in line with a previous study where general astroglial cytoskeletal atrophy was observed, while GFAP+ astrocytes surrounding Aβ plaques were hypertrophic in the HPC of 18-month-old 3xTG AD mice [77]. Given that astrocytes do not migrate to amyloid plaques [78], current data suggests that astrocytes near plaques are induced to upregulate GFAP expression, while astrocytes in the rest of the HPC downregulate GFAP. As many extracellular factors, e.g., inflammatory factors, can affect transcription and translation of GFAP [79,80], microenvironmental changes induced by plaque accumulation may lead to local dynamic alterations in GFAP expression.…”
Section: Modulation Of Astrocytes By Aβ Overexpression In Hpc and Ecsupporting
confidence: 91%
“…The reduction in global versus the increase in clustered GFAP coverage is in line with a previous study where general astroglial cytoskeletal atrophy was observed, while GFAP+ astrocytes surrounding Aβ plaques were hypertrophic in the HPC of 18-month-old 3xTG AD mice [77]. Given that astrocytes do not migrate to amyloid plaques [78], current data suggests that astrocytes near plaques are induced to upregulate GFAP expression, while astrocytes in the rest of the HPC downregulate GFAP. As many extracellular factors, e.g.…”
Section: Modulation Of Astrocytes By Aβ Overexpression In Hpc and Ecsupporting
confidence: 91%
“…The reduction in global versus the increase in clustered GFAP coverage is in line with a previous study where general astroglial cytoskeletal atrophy was observed, while GFAP + astrocytes surrounding Aβ plaques were hypertrophic in the HPC of 18-month-old 3xTG AD mice [76]. Given that astrocytes do not migrate to amyloid plaques [77], current data suggests that astrocytes near plaques are induced to upregulate GFAP expression, while astrocytes in the rest of the HPC downregulate GFAP. As many extracellular factors, e.g.…”
Section: Modulation Of Astrocytes By Aβ Overexpression In Hpc and Ecsupporting
confidence: 91%